Analisis Konsep Dasar Menulis Permulaan Pada Siswa Kelas 1 Di Sekolah Dasar - Sholihah, Alviyatus; Ummatin, Siti Khoiru; Khoiroh, Yatimatul; Mas’odi, Mas’odi (Peneliti.net, 2025)
The basic principles of writing begin by introducing letters to students, followed by practice writing loose letters. Writing skills are taught in class I to improve students' writing skills. Factors that influence the writing process include learning difficulties, sensory and social disorders, and learning process incompatibility. Obstacles to writing in grade 1 include intellectual factors, family environment, motivation, and low interest in reading. Teachers use strategies such as word paste media, cursive letters, and letter recognition exercises to overcome students' reading and writing difficulties.